2016
DOI: 10.1111/jfd.12574
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Shewanella putrefaciens group in wild eels Anguilla anguilla L. favoured by hypoxic aquatic environments

Abstract: Microbiological analyses were conducted on wild eels from the L'Albufera Lake (Spain). A total of 174 individuals were collected in two surveys (i.e. year 2008 and autumn-winter 2014) among those caught by local fishermen into the lagoon. The prevalence of Shewanella putrefaciens group was 1.7% in 2008 and rose above 32% in 2014. It was due to an outbreak of shewanellosis that presented a morbidity rate of 64%. S. putrefaciens group strains were isolated as pure cultures from the sick eels that showed white ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 21 publications
4
44
0
Order By: Relevance
“…First, the bacterium has never been associated with epizootic diseases occurring in fish farms from this Mediterranean region (Biosca, Amaro, Esteve, Alcaide, & Garay, ; Esteve et al., ; Fouz, Roig, & Amaro, ). Second, the historical series of edwardsiellosis at the L′Albufera Lake (2003, 2004, 2005, 2008 and 2014 surveys), with total prevalence values ranging from 5%–11.8% (Esteve & Alcaide, ; Esteve et al., ; present study), better indicated that edwardsiellosis could be a native bacterial disease. However, neither this long incidence period nor the prevalence values observed fit with the “outbreak” concept, in contrast to that observed for other bacterial diseases (Esteve et al., , ).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…First, the bacterium has never been associated with epizootic diseases occurring in fish farms from this Mediterranean region (Biosca, Amaro, Esteve, Alcaide, & Garay, ; Esteve et al., ; Fouz, Roig, & Amaro, ). Second, the historical series of edwardsiellosis at the L′Albufera Lake (2003, 2004, 2005, 2008 and 2014 surveys), with total prevalence values ranging from 5%–11.8% (Esteve & Alcaide, ; Esteve et al., ; present study), better indicated that edwardsiellosis could be a native bacterial disease. However, neither this long incidence period nor the prevalence values observed fit with the “outbreak” concept, in contrast to that observed for other bacterial diseases (Esteve et al., , ).…”
Section: Discussionsupporting
confidence: 57%
“…The other bacterial diseases recorded in this fishery had an overall prevalence of 25.3% (i.e., aeromonosis [15.7%], shewanellosis [1.7%] and vibriosis [7.9%]). Shewanella putrefaciens (data in Esteve et al., ), V. vulnificus and motile Aeromonas were isolated as pure cultures from liver/kidney samples obtained from these sick fish, but mostly on TSA‐1 plates (Figure ). Interestingly, the intestine samples obtained from almost any sick wild eel yielded the isolation of E. tarda/piscicida using the selective enrichment procedure (Figures and ; Supporting Information Table S3).…”
Section: Resultsmentioning
confidence: 93%
“…Shewanella spp ., gammaproteobacteria belonging to the Alteromonadaceae family, are widespread in marine and freshwater environments (Buller, ). Different Shewanella species were isolated from healthy fish as well as from fish exhibiting clinical signs of a disease (Al‐Harbi & Uddin, ; Cocchi et al, ; Esteve, Merchán, & Alcaide, ; Jung‐Schroers et al, ; Kim et al, ; Korun, Akgun‐Dar, & Yazici, ; Pakingking, Palma, & Usero, ; Pękala, Kozińska, Paździor, & Głowacka, ; Qin, Zhu, & Xu, ; Rusev, Rusenova, Simeonov, & Stratev, ; Saeed, Alamoudi, & Al‐Harbi, ). However, contemporary typing methods were not sufficient to determine genotypic diversity of Shewanella fish isolates.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the pure bacterial growth of S. putrefaciens group from kidney, skin and CNS apparently confirms the ability of the microorganism to cause a septicaemic spread and suggests the presence of potential virulence factors involved in the pathogenetic mechanisms (Paździor, ). To the best of our knowledge, API 20E system numeric profile 0402004 of our isolate was previously recorded both in farmed and wild species, but not in koi ( Cyprinus carpio L.) (Esteve et al., ; Pękala et al., ).…”
Section: Bacterial Isolation Resultsmentioning
confidence: 80%
“…The first isolation related to health disorders in freshwater fishes dates back to 2004 in Poland; since then, episodes of infection have been reported in different fresh and saltwater species, including koi (Cyprinus carpio L.). Skin necrotizing and ulcerative lesions and gill necrosis are the main gross pathologic findings, and polymicrobic infections have been recorded (Altun et al, 2014;El-Barbary, 2017;Esteve, Merchán, & Alcaide, 2017;Korun, Akgun-Dar, & Yazici, 2009;Kozińska & Pękala, 2004;Paździor, 2016;Pękala et al, 2015;Qin, Zhu, & Xu, 2014;Rusev, Rusenova, Simeonov, & Stratev, 2016).…”
mentioning
confidence: 99%